Ecology and population assessment of Megachile cypricola Mavromoustakis, 1938 (Hymenoptera, Megachilidae), a threatened bee endemic to Cyprus - Santerre, Rémi; Benrezkallah, Jordan; Varnava, Androulla I.; Michez, Denis; Stavrinides, Menelaos (My University, 2025)
Megachile cypricola is a solitary bee endemic to Cyprus, assessed as Critically Endangered in 2014 following IUCN criteria. Recent records suggest that the species is still occurring in a few locations, however information on its ecology and population size is required to revise its status and implement conservation measures. For this purpose, samplings were carried out in four areas during spring 2022. We evaluated: (i) the habitat of M. cypricola; (ii) its foraging ecology and the importance of Onobrychis venosa (endemic Fabaceae reported as its main host-plant) in its diet; (iii) its nesting biology; (iv) its population size. We observed M. cypricola in mediterranean shrublands growing on limestone. O. venosa represented over 95% of the female pollen loads on average, confirming its narrow oligolecty. The nests consisted of external structures made of a dried mortar of sand and secretions regurgitated. A mark-recapture study resulted in an estimate of 849.4 female individuals across three assessment locations. Overall, the study highlights the high degree of specialisation of M. cypricola on a single endemic plant species. It also provides evidence that the species, only known from a restricted number of localities, is relatively abundant locally.
Keywords: Solitary bee; Threatened species; Conservation; Foraging ecology; Population size; Endemism